Implementation of Process Standards in Improving the Quality of Learning at Pelita Hati Special School Pekanbaru - Cici Murni; Rahmat Fahmi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to analyze the implementation of process standards in improving the quality of learning at SLB Pelita Hati Pekanbaru. Process standards are a crucial component in the education system, particularly in the context of special education, which requires adaptive, flexible, and student-centered learning approaches. This research employed a descriptive qualitative approach with data collected through interviews, observations, and documentation. The findings reveal that the implementation of process standards is carried out through lesson planning based on the Merdeka Curriculum, adaptive teaching practices tailored to students’ characteristics, and continuous individualized assessment. Furthermore, parental involvement and teacher professional development through training programs play a significant role in enhancing learning quality. However, challenges remain in terms of instructional differentiation and resource limitations. Overall, the implementation of process standards has positively contributed to improving learning quality, although further strengthening in pedagogical innovation and multi-stakeholder collaboration is required.